Effect of selected starter cultures on physical, chemical and microbiological characteristics and biogenic amine content in Protected Geographical Indication Ciauscolo salami - David Ranucci; Anna Rita Loschi; Dino Miraglia; Roberta Stocchi; Raffaella Branciari; Stefano Rea (Italian Journal of Food Safety, 2016)
The aim of the study was to evaluate the biogenic amine (BA) content of Ciauscolo salami made with and without the use of a selected started culture. Two batches of salami were made following the guidelines of the Protected Geographical Indications: with and without adding a commercial starter culture made of Lactobacillus plantarum and Staphylococcus xylosus. Six samples of salami per batch were collected at different ripening times (0, 15, 30, 45 and 60 days) for physical, chemical and microbiological analyses and for the determination of BA content. No differences were recorded for physical, chemical and microbiological analyses except for Staphylococcus spp. count at the time of casing (T0) and total volatile basic nitrogen (TVBN) from 30 days (T2) to the end of the ripening time (60 days, T4). After 60 days of ripening, the use of selected starter culture significantly affected the amount of putrescine (195.15 vs 164.43 mg/100 g in salami without and with starters, respectively), cadaverine (96.95 vs 104.40 mg/100 g in salami without and with starters, respectively), histamine (81.94 vs 69.89 mg/100 g in salami without and with starters, respectively), and spermine (36.88 vs 33.57 mg/100 g in salami without and with starters, respectively). Despite significantly higher values of TVBN, the use of selected starter culture determined no significant effects on the BA content of the products.